Development of an In Vitro Drug Release Method to Enable In Vitro–In Vivo Correlation of Potassium Chloride Extended-Release Tablets - Qiu, Yihong; Zhu, Donghua Alan; Apfelbaum, Kathleen; Zu, Hui; Xiong, Hao (Molecular pharmaceutics, 2022)
An in vitro drug release test was developed to establish a level A in vitro–in vivo correlation (IVIVC) for predicting the in vivo performance of potassium chloride extended-release (ER) matrix tablets. Three ER formulations of potassium chloride with different in vitro release rates were designed using the USP dissolution test, and their urinary pharmacokinetic profiles were evaluated in healthy subjects. Due to the lack of IVIVC with the USP method, experiments were designed to investigate the effects of in vitro test conditions on drug release in order to match in vitro drug release with in vivo behaviors of different formulations. The evaluated in vitro variables included the type of USP apparatus, surfactant, and ionic strength of the dissolution medium. Based on the study findings and data analysis, a discriminatory drug release method was successfully developed that enabled the establishment and validation of a level A IVIVC model of the potassium chloride ER tablet using urinary pharmacokinetic data. This method uses USP apparatus I at 50 rpm in 900 mL of 150 mM NaCl solution containing 40 mM sodium dodecyl sulfate at 37 °C. The current study highlights the value of investigating test conditions in developing a predictive in vitro test method for establishing IVIVC.